Recent Trends in Adolescent Alcohol Use in Hawai‘i: 2005–2011 - Nigg, Claudio R (University Clinical, Education & Research Associate (UCERA), 2013)
Monitoring trends in adolescent alcohol use over time is important for planning, allocation of resources, and evaluation of alcohol prevention and treatment programs. This article is an update of previously reported trends in adolescent alcohol use in the State of Hawai‘i utilizing data from the Centers for Disease Control and Prevention's Youth Risk Behavior Survey. Five alcohol use indicators were investigated between 2005 and 2011 including lifetime use, onset age, current use, binge drinking, and drinking on school property. Youth in Hawai‘i generally reported worse alcohol behaviors in 2009 compared to 2007 but better alcohol use behaviors were observed in 2011 compared to 2009. This trend was not observed on the national level and thus may represent changes unique to Hawai‘i. These apparent changes in alcohol use among adolescents highlight the need for resources and for continued surveillance.